Technological Capability in Industry 4.0: A Literature Review for Small and Medium Manufactures Challenges - Ahmad, Nurazwa; Azman, Nurul Afiqah (ADVANCE SCIENTIFIC RESEARCH, 2020)
Technological capabilities work as a basis for one to adapt and compete with the rapid pace of Industry 4.0 as without it worried the industry would get left behind hence this paper intends to give the low-down on the issues encountered regarding the technological capabilities in small and medium manufacturing enterprise (SME) due to the rise of Fourth Industrial revolution in manufacturing industry. Methods used are by reviews the literature on technological capabilities in the manufacturing sector based on journal articles, online news and books that strictly related to the keywords and research area. The concerns encountered in this paper are regarding the components of technological capabilities, and the challenges of technological capabilities face by manufacturers SME in Malaysia. Although a lot of researches uncover only the ground of technological capabilities hence there is a need to hit the books on the research area. Both empirical and non-empirical must carry out to discover more issues related to technological capabilities, and the study only covers the small and medium manufacturing enterprises in Malaysia.